THE IMPACT OF DIGITAL TRANSFORMATION ON EXPORT MARKETING IN THE B2B MARKET OF TEXTILE ENTERPRISES - Sapayeva, Nilufar Kadambayevna (THE INNOVATION ECONOMY, 2026)
The article systematically examined the impact of digital transformation on export marketing of textile enterprises in the B2B market. The study established the relationship between digital capabilities, firm digital maturity, and export marketing performance based on a conceptual model. The role of B2B platforms, CRM systems, artificial intelligence, blockchain, and IoT technologies in export processes was identified. The findings showed that digital integration improved market segmentation accuracy, customer trust, and operational efficiency. The research defined evidence-based directions for enhancing digital export strategies in the textile industry of Uzbekistan.